2020
DOI: 10.1177/1934578x19878904
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibility of Multidrug Resistant Strains of Salmonella to Essential Oils

Abstract: Antimicrobial resistance has become a global threat to public health. There is a critical need to find new antimicrobial substances from natural sources. The aim of this study was to investigate the antimicrobial activity of essential oils (EOs) obtained from Origanum vulgare, Thymus serpyllum, Thymus vulgaris, and Melaleuca alternifolia against multidrug resistant strains of Salmonella isolated from samples of diverse animal origin. The strains were biochemically identified, serotyped, and characterized for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Among essential oils, oregano essential oil (ORE) is used in the pig industry for its beneficial effects, ranging from improved performance to increased pork quality ( 31 , 32 ). It has been shown that oregano has anti-inflammatory and antimicrobial effects ( 33 35 ), by modulating the cytokine levels and immunity-related transcription factors ( 36 , 37 ). In addition, oregano stimulates digestion with effects on enterocytes, by accelerating their renewal rate, improving their capacity for nutrient absorption, and reducing pathogen contamination ( 38 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among essential oils, oregano essential oil (ORE) is used in the pig industry for its beneficial effects, ranging from improved performance to increased pork quality ( 31 , 32 ). It has been shown that oregano has anti-inflammatory and antimicrobial effects ( 33 35 ), by modulating the cytokine levels and immunity-related transcription factors ( 36 , 37 ). In addition, oregano stimulates digestion with effects on enterocytes, by accelerating their renewal rate, improving their capacity for nutrient absorption, and reducing pathogen contamination ( 38 ).…”
Section: Introductionmentioning
confidence: 99%
“…The microdilution method in 96-well plates revealed MIC and MBC values of 0.156 and 0.3125 μg mL -1 , respectively. Another investigation assessed the antibacterial activity of oregano oil using both disk diffusion and broth microdilution techniques against 25 strains of Salmonella isolated from turkey, chicken, calf burgers, and wild boar liver (Listorti et al, 2020). Inhibition zones ranging from 10.3 to 23.3 mm in diameter were observed, along with MIC and MBC values ranging from 0.012 to 0.2 %v/v (Listorti et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, organo essential oil act as anti-inflammatory by inhibiting the inflammatory biomarkers levels; monocyte chemoattractan protein-1 (MCP-1), the vascular cell adhesion molecule-1 (VCAM-1) and the intracellular cell adhesion molecule-1 (ICAM-1) (MCP-1, VCAM-1 and ICAM-1), and decrease synthesis of cytokines; tumor necrosis factor-alpha (TNF-α), interleukin (IL)-6, IL-1β, and IL-6 and Increased synthesis of cytokine IL-10 [22]. So, oregano has antiinflammatory and antimicrobial effects [52], by modulating the cytokine levels and immunityrelated transcription factors [28]. Also, carvacrol reduces the severity of inflammation by the production of mediators of inflammation and protein concentration as well as the gene expression modulation of interleukins [53].…”
Section: Discussionmentioning
confidence: 99%